Prevalence and healthcare costs associated with the management of diabetic foot ulcer in patients attending Ahmadu Bello University Teaching Hospital, Nigeria - Danmusa, Umar Mukhtar; Terhile, Iorliam; Nasir, Idris Abdullahi; Ahmad, Auwal Alkasim; Muhammad, Habiba Yahaya (International Journal of Health Sciences, 2016)
Introduction: Diabetic foot ulcers (DFU) are non-traumatic lesions of the skin on feet of diabetic patients. DFU require appropriate investigations, dietary placement and clinical management. These constitute huge healthcare costs in DFU care. Objective: This study sought to determine the prevalence of DFU in relation to clinical, sociodemographic variables and healthcare costs expended. Methods: This was a retrospective study. Hence, medical records and healthcare costs of 1573 DFU-diagnosed patients who visited the diabetic clinic and medical wards of Ahmadu Bello University Teaching Hospital, Nigeria were reviewed and analyzed for relevant data. Results: The prevalence of DFU in patients with diabetic mellitus (DM) was 6.0% with more cases in men (67.2%) than women (32.8%). The prevalence of DFU in relation to type of DM was 6.5% and 0% for DM type-II and DM type-I respectively. The distribution of DFU in relation to clinical stages was 40%, 25.7%, 17.1% and 11.4% for stages-IV, III, II and I. Patients in the age group 51-60 years had the highest frequency of DFU (28.6%), but there was no DFU in those 10-20 years and > 80 years. It required an average of 1808 US$ to successfully treat patients with DFU stage IV, while 1104 US$ and 556 US$ was required to treat DFU stage III and II respectively. Cost of procuring drugs covered the highest burden of total healthcare cost in managing DFU (35%-46%). Conclusion: The prevalence of DFU in DM patients attending ABUTH was high. Healthcare costs associated with DFU especially cost of drugs procurement contributed the highest financial burden in managing DFU. Keywords: Diabetic mellitus, Diabetic foot ulcer, Financial costs, Chemotherapy, Nigeria.